Assessing the Low Engagement of Youth and Children in Church Ministry at Rwabukoba C.O.U Parish, Kashenyi Archdeaconry, North Kigezi Diocese - Nicholas Turyahabwe (Uganda Christian University, 2025)
This study assessed the factors contributing to the low engagement of youths and Children in Church ministry at Rwabukoba COU Parish, Kashenyi Archdeaconry, North Kigezi Diocese, and propose strategies to enhance their active participation. It was guided by the following objectives; to evaluate the extent to which the Church actively engages the next generation (youths and Children) in ministry and leadership roles, to identify the key factors contributing to the low participation of youths and children in Church ministry and to develop and implement targeted programs that foster intergenerational connections within the Church and extend these initiatives to the broader community. The study utilized a quantitative research approach and data was collected from a sample of 80 respondents using both the questionnaire and interview methods. From the study, it was found that the evaluation of youth and children’s engagement in ministry and leadership roles at Rwabukoba COU Parish reveals a significant gap between the Church’s potential and its current practice in nurturing the next generation. Through systematic assessment, it becomes evident that while the Church possesses the structural framework and theological foundation to actively involve young people in meaningful ministry roles, the practical implementation remains limited. The research demonstrates that current engagement levels fall short of creating sustainable pathways for youth and children to participate meaningfully in Church leadership, worship activities, and community service initiatives. This limited engagement not only affects the immediate spiritual development of young congregants but also threatens the long-term vitality and continuity of the parish’s mission and vision. The identification of key factors contributing to low participation among youth and children reveals a complex interplay of cultural, structural, and relational barriers that must be addressed holistically. Primary contributing factors include traditional hierarchical church structures that inadvertently exclude younger voices, limited age-appropriate programming and worship opportunities, insufficient mentorship and discipleship programs, and a disconnect between contemporary youth culture and traditional church practices. The development and implementation of targeted intergenerational programs emerge as crucial solutions that can bridge existing gaps and create sustainable engagement pathways for the broader community. The research findings indicate that successful youth and children engagement requires intentional programming that honors both traditional church values and contemporary relevance, creating spaces where different generations can learn from and contribute to one another. From the findings of the study, it was recommended that the department should create age-appropriate leadership tracks that provide meaningful responsibilities, decision-making authority, and skill development opportunities within the church structure. The parish must implement regular assessment mechanisms including quarterly engagement surveys, participation tracking systems, and feedback sessions to monitor progress and adjust strategies accordingly. Additionally, the church should develop a formal mentorship program pairing experienced adult leaders with emerging youth leaders, ensuring knowledge transfer and providing supportive guidance for young people stepping into ministry roles. This structural transformation should include establishing youth-led worship services, children’s ministry teams, and community outreach programs that give young people authentic ownership and responsibility in church operations.
General Objective To assess the factors contributing to the low engagement of youths and Children in Church ministry at Rwabukoba COU Parish, Kashenyi Archdeaconry, North Kigezi Diocese, and propose strategies to enhance their active participation. Objectives 1. To evaluate the extent to which the Church actively engages the next generation (youths and Children) in ministry and leadership roles 2. To identify the key factors contributing to the low participation of youths and children in Church ministry 3. To develop and implement targeted programs that foster intergenerational connections within the Church and extend these initiatives to the broader community